The Nightmare dilemma - Arnett, Mindee (Tor Teen, 2014)
When a mermaid is viciously assaulted and left for dead, the accused Lance Rathbone asks Dusty Everhart to find the real attacker and, meanwhile, Dusty's ex-boyfriend returns and the Magi Senate wants her to discover his true motives, infuriating her friend Eli.